Pelatihan Media Pembelajaran Menggunakan Konteks Wisata Lokal Bagi Guru Matematika - Idul Adha; Rani Refianti; Anna Fauziah; Sukasno Sukasno; Maria Luthfiana (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2025)
The training of learning media using the context of local tourism for mathematics teachers was carried out with the aim of improving the ability of teachers in compiling learning media using the context of local tourism that is familiar to students so that it can facilitate the learning process in the classroom, in addition, with this activity a teacher can have more experience in designing or planning a learning media that is in accordance with the student's residential environment, furthermore through this activity can provide a more meaningful mathematics learning experience to students, where mathematics is really linked to things that students often encounter. The methods used in this activity are discussion, lecture and demonstration, the results of data analysis in the form of a response questionnaire. Based on the results of the calculation of the response questionnaire to the training, a percentage score of 92.625% was obtained